2021
DOI: 10.3390/v13081649
|View full text |Cite
|
Sign up to set email alerts
|

Serological Detection of SARS-CoV-2 Antibodies in Naturally-Infected Mink and Other Experimentally-Infected Animals

Abstract: The recent emergence of SARS-CoV-2 in humans from a yet unidentified animal reservoir and the capacity of the virus to naturally infect pets, farmed animals and potentially wild animals has highlighted the need for serological surveillance tools. In this study, the luciferase immunoprecipitation systems (LIPS), employing the spike (S) and nucleocapsid proteins (N) of SARS-CoV-2, was used to examine the suitability of the assay for antibody detection in different animal species. Sera from SARS-CoV-2 naturally-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Recently, another multispecies ELISA based on the detection of antibodies against the receptor-binding domain (RBD) of SARS-CoV-2 has been developed with a specificity of 100% and sensibility of 98.3% (Wernike et al, 2020). In addition, the luciferase immunoprecipitation systems (LIPS), employing the spike, gave good results in experimentally infected ferrets (Berguido et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another multispecies ELISA based on the detection of antibodies against the receptor-binding domain (RBD) of SARS-CoV-2 has been developed with a specificity of 100% and sensibility of 98.3% (Wernike et al, 2020). In addition, the luciferase immunoprecipitation systems (LIPS), employing the spike, gave good results in experimentally infected ferrets (Berguido et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that measuring ACE2 interactions with SARS-CoV-2 may not be a perfect method for predicting a species susceptibility to infection, progression to disease, and even viral transmission. For instance, both in silico and in vitro studies have suggested that ferrets and mink ACE2 interacts poorly with S-protein [6,9,48], however these animals are readily infectible with SARS-CoV-2, often dramatically so [49][50][51][52]. As the field progresses, it will behoove us to think not only of ACE2 but other physiological differences between species which may impact SARS-CoV-2 susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Various luciferase genes have been used as the reporter gene in LIPS assays, including Renilla luciferase ( Berguido et al., 2021 ; Hachim et al., 2022 ), NanoLuciferase ( Honda et al., 2021 ), and GLuc ( Honda et al., 2021 ). GLuc from the marine copepod Gaussia princeps is naturally secreted from mammalian cells in an active form and can be released efficiently into the conditioned medium of mammalian cells ( Tannous, 2009 ).…”
Section: Discussionmentioning
confidence: 99%